Pendidikan Islam Dalam Konsep Prophetic Intelligence - Hayat, Hayat (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
Intelligence has connectivity to the educational process as a concrete step in the development of human character as caliph fil ardl to think of all God ‘s creation. Islamic education teaches a life of meaning to the concept of “amar ma’ruf nahi mungkar”. It is really clear that various concepts in Islamic education are not adjusted enough with the development period that is increasingly sophisticated and globalized. Islamic civilization has been built since the Prophet Muhammad SAW, and other thinkers in teaching a sense of knowledge that is based on Al- Quran and Al - Hadits as the main guideline. Intelligence Prophetic provides illustration that in transforming education through the concrete steps for being “insan Kamil” that is “rahmatan lil alamin”. Intelligence Prophetic provides illustration that in transforming education through the concrete steps for being ‘insan Kamil’ that is ‘rahmatan lil alamin’.